Examining the risk of delirium in patients hospitalized with COVID-19: Insights from the homeless population - Liam O’Neill; Neale R. Chumbler (PLoS ONE, 2025)
For patients hospitalized with COVID-19, delirium is a serious and under-recognized complication, and people experiencing homelessness (PEH) may be at greater risk. This retrospective cohort study compared delirium-associated risk factors and clinical outcomes between PEH and non-PEH. This study used patient records from 154 hospitals discharged from 2020–2021 from the Texas Inpatient Public Use Data file. Study subjects (n = 878) were patients, aged 18–69 years, who were hospitalized with COVID-19 and were identified as homeless. The baseline group included (n = 176,518) patients with COVID-19 aged 18–69 years who were not homeless. Logistic regression models were used to identify risk factors for delirium. Relevant risk factors included chronic comorbidities, substance use disorders, and traumatic brain injury (TBI). Seven of the delirium-associated risk factors were more prevalent among PEH compared to baseline. PEH had higher rates of TBI, alcohol, cannabis, and opioid use disorders. PEH had significantly higher rates of delirium (10.6% vs. 8.1%; P<0.01). However, PEH had fewer respiratory complications, including pneumonia (48.5% vs. 81.9%; P<0.001) and respiratory failure (28.7% vs. 61.9%; P<0.001), and lower in-hospital mortality (3.3% vs. 9.5%; P<0.001). The anti-viral Remdesivir had a protective effect against delirium (AOR = 0.63; CI: 0.60, 0.66). Mean hospital length of stay (LOS) was more than twice as long for delirious patients compared with non-delirious patients (18.4 days vs. 7.7 days; P<0.001). Delirium greatly increased the risk of in-hospital mortality (AOR = 3.8; CI: 3.6, 4.0). For PEH (n = 29) who died from COVID-19, delirium was present in more than half (52%) of cases. Hospitals should screen PEH for delirium and adopt nursing protocols to prevent delirium and reduce its severity.